Acute clinical manifestations in toxic smoke inhalation victims: systematic review of observational studies - Damiana Lima Costa; Tamires Daros dos Santos; Amanda Albiero Real; Graciele Sbruzzi; Adriane Schmidt Pasqualoto; Isabella Martins de Albuquerque (Editora Champagnat, 2018)
Abstract Introduction: Lung injuries from toxic smoke inhalation are the main causes of death in fire victims; however, information regarding the acute effects on the respiratory system after smoke inhalation and its constituents in closed environments are still scarce in literature. Objective: To investigate the acute clinical manifestations observed in victims of smoke inhalation during enclosed-space fires by means of systematic review. Methods: A systematic search was conducted in the following databases: MEDLINE (via PubMed), Lilacs, Scopus and Web of Science. There were no appliedrestrictions in terms of thepublication date. In addition, a manual search was performed on the references of published studies. Observational studies assessing the prevalence of acute clinical manifestations in victims of toxic smoke inhalation in closed environments were included. Results: Of the 4,603 articles identified, eight were included, comprising a total of 233 patients. The signs and symptoms were identified and ranked according to frequency. Dyspnea (58.80%, six studies), carbonaceous sputum (54.51%, four studies), hoarseness (39.91%, three studies), wheezing (34.33%, five studies) and sore throat (33.90%, two studies) were the most frequent acute clinical manifestations of smoke inhalation. Besides these, chest pain and pulmonary edema were observed, respectively in 13.30%, 5.15% of the studies. Conclusion: The results suggest that dyspnea, carbonaceous sputum, hoarseness, wheezing and sore throat were the most frequent acute clinical manifestations in victims of smoke inhalation. Further studies of a higher level of evidence and greater methodological rigor are required.